Molecular detection of Babesia and Hepatozoon species and morphological characteristics of Babesia species in Japanese wild boars - Shiho Ohmori; Motoko Nagano-Fujii; Kazuo Suzuki; Masataka Korenaga; Fumi Murakoshi; Atsuko Saito-Ito (International Journal for Parasitology: Parasites and Wildlife)
We investigated intraerythrocytic Babesia parasites in 21 Japanese wild boars, Sus scrofa leucomystax, captured in Wakayama Prefecture on the mainland from 2008 to 2009 and in 31 Japanese wild boars from 2011 to 2013 in Kochi Prefecture on Shikoku Island, Japan. We detected small subunit ribosomal RNA (18S rRNA) gene (SSUrDNA) fragments of a Babesia species in 17 boars from Wakayama and 18 boars from Kochi. The nearly full SSUrDNA sequence (1669 bps) of this species was determined. A FASTA search revealed that the SSUrDNA sequence of the Babesia sp. in Japanese wild boars was the most homologous to those of several Babesia isolates reported as Babesia gibsoni. Phylogenetic analysis showed that the Babesia sp. found in Japanese wild boars was the closest relative to B. gibsoni but made a different clade from B. gibsoni. The Babesia sp. in Japanese wild boars was completely different from Babesia sp. Suis found in a European domestic pig, Sus scrofa domesticus. By microscopic examination, ring-shaped, oval and pear-shaped small sized intraerythrocytic parasites were observed on blood smears of 12 of 18 Japanese wild boars whose blood smears could be examined in Wakayama. We also detected SSUrDNA fragments of a Hepatozoon species in 6 of the 21 wild boars from Wakayama. The nearly full SSUrDNA sequence (1774 bps) of the Hepatozoon sp. was shown to be identical to that of Hepatozoon apri.